THE COURSE OF THE PEOPLE’S LIBERATION STRUGGLE UNDER MUHAMMAD-AMIN’S COMMAND IN THE NORTH-WEST CAUCASUS IN THE 50s OF THE 19th CENTURY - Kidirniazov, D S (History, Archeology and Ethnography of the Caucasus, 2017)
Liberation struggle of mountaineers of the North Caucasus in the first half of the 19th century has always been one of the most topical problems in Russian historiography, since an integral, truthful and genuinely scientific concept of the events, which played an important role in the destinies of the peoples of the region, has not been created yet. It is known that the assessment of the Caucasian War has been changed many times. The researchers have misrepresented events and slanted a number of problems in the history of the local peoples and their relationship with Russia. The history of long heroic and at the same time tragic struggle of the mountaineers for freedom and independence is complex and unique. The people’s liberation movement arose due to socio-economic and political situation in the region, although intrigues of emissaries of other states also influenced the mountaineers’ struggle. The main reasons for the people’s liberation struggle appeared in the North-East Caucasus when the socio-political situation in the region had considerably changed. Basing on archival materials and special historical literature, the author of the article analyzes the liberation struggle of the mountaineers of the North-West Caucasus against the tsarist autocracy under the command of Shamil’s Naib Muhammad-Amin. The goal of the article is to trace the course of the people’s liberation struggle in the North-West Caucasus and its legal aspects in terms of both positive and negative sides. The author focuses on administrative and commanding talent of Muhammad-Amin, who managed to rally the mountaineers and organize the people’s liberation movement.
Keywords: Russia; North-West Caucasus; government; peoples; people’s liberation movement; troops; command